2009
DOI: 10.5007/2175-8077.2009v11n23p192
|View full text |Cite
|
Sign up to set email alerts
|

Modelos de retornos esperados no mercado brasileiro: testes empíricos utilizando metodologia preditiva

Abstract: Metodologias preditivas para teste de modelos de retornos esperados são amplamente difundidas no meio acadêmico internacional, entretanto, não têm sido sistematicamente aplicadas no Brasil. Geralmente, os estudos empíricos procedidos com dados do mercado acionário brasileiro concentram-se apenas na primeira etapa dessas metodologias. O objetivo deste artigo foi testar e comparar os modelos CAPM (Capital Asset Pricing Model), 3-fatores e 4-fatores a partir de uma metodologia de teste preditivo, utilizando duas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
(15 reference statements)
1
8
0
9
Order By: Relevance
“…Two portfolios had significant Jensen's alphas with p < 0.05, suggesting that the three-factor model still lacks explanatory power. These results are similar to those found by other Brazilian studies, including Málaga and Securato (2004), Mussa et al (2007), and Mussa et al (2009).…”
Section: The Fama and French Three-factor Modelsupporting
confidence: 93%
“…Two portfolios had significant Jensen's alphas with p < 0.05, suggesting that the three-factor model still lacks explanatory power. These results are similar to those found by other Brazilian studies, including Málaga and Securato (2004), Mussa et al (2007), and Mussa et al (2009).…”
Section: The Fama and French Three-factor Modelsupporting
confidence: 93%
“…Málaga and Securato (2004) obtained results that confirmed the superiority of the three factor model in relation to the CAPM in explaining returns on Brazilian shares. Mussa, Rogers, and Securato (2009) produced a paper in which they tested the predictive ability of the CAPM and the three factor model, carrying out the two stage procedure in accordance with Fama and MacBeth (1973) and concluded that neither of the two models is efficient in predicting returns on Brazilian shares, given the significance observed in the regression intercepts.…”
Section: E(r I ) -R F = B I (R M -R F ) + S I (Smb) + H I (Hml) + W Imentioning
confidence: 99%
“…The size (SMB) of the risk premium does not present any positive and statistically 1 Fama and French (1998), Rouwenhorst (1999), Bonomo and Garcia (2001), Bonomo, Pereira and Schor (2002), Sampaio (2002), Malaga and Securato (2004), Matos (2006), Chague and Bueno (2007), Bellizia (2009), Mussa, Rogers and Securato (2009), Brito and Murakoshi (2009), Mussa et al (2011), Bodur (2011), Rizzi (2012), Mussa, Fama and Santos (2012), Varga and Brito (2015), Eid Jr and Martins (2015), and Piccoli et al (2015).…”
Section: Figure 1 -Dispersion In the Risk Premia Estimations For Brazilmentioning
confidence: 93%